The Future of Spa Cities: Integration of Traditional and Artificial Intelligence-based Tools for Sustainable Tourism on the International Level and in Hungarian in the Light of a Literature Review - Fejes, Judit Katalin; Katits, Etelka; Szabó, Zoltán (Acta Carolus Robertus, 2025)
Spa towns face new challenges due to the 21st century’s global tourism demands and sustainability requirements. Traditional management tools are no longer sufficient to meet the rapidly changing needs of modern tourism. This research aims to evaluate the specific effectiveness of traditional and Artificial Intelligence (AI)-driven management tools in both international and Hungarian contexts, with particular attention to settlement characteristics and the unique challenges of tourism. The results suggest that a combination of traditional and AI-driven tools offers an effective solution to enhancing the sustainability and competitiveness of spa towns. The study places special emphasis on addressing differences of the spa towns and examining the social and ethical impacts of AI-driven tools.